Translation and psychometric evaluation of the Chinese version of the arterial puncture self-efficacy scale - Qiuyan Li; Dian Wang; Wenjun Luo; Xiaoling He; Hongjuan Huang (BMC Nursing)
Abstract Background Arterial blood gases (ABG) analysis is an indispensable yet difficult-to-perform skill in nursing practice. In the acquisition of this skill, nurses’ self-efficacy plays a crucial role. Nevertheless, there is presently a shortage of a dependable tool for assessing the self-efficacy of Chinese nurses when it comes to performing arterial punctures for ABG analysis. Objectives To translate and psychometrically validate the Arterial Puncture Self-Efficacy Scale (APSES) for health professionals in China. Methods A cross-sectional methodological study was employed. From January 2022 to September 2022, a convenience sample of 304 nurses was recruited from Sun Yat-sen Memorial Hospital through an online questionnaire. Internal consistency reliability, test-retest reliability, split-half reliability, construct validity, and content validity of the APSES-C were analyzed using psychometric testing. Results The APSES-C retained 16 items after modification and comprises two components: preparation of patient and material, and arterial puncture and sample management. Overall, the APSES-C indicated acceptable internal consistency coefficients (Cronbach’s α: 0.86), a good test-retest reliability within a 4-week interval (intraclass correlation coefficient: 0.75), and satisfactory content validity (I-CVI = 0.8-1.0, S-CVI = 0.95). Confirmatory factor analysis revealed that the modified two-factor structure of the 16-item APSES-C presented a good model fit to the data analysis revealed that the modified two-factor structure of the APSES-C presented a good model fit to the data. Conclusions This study suggested that the 16-item APSES-C is a reliable tool for assessing Chinese health professionals’ self-efficacy toward arterial punctures for ABG analysis, which may help enhance arterial puncture skills in the context of Chinese nursing practice. The APSES-C may serve as a practical tool for nursing educators to identify skill gaps in arterial puncture training and develop targeted interventions to enhance clinical competence among Chinese nurses.